HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL DENGAN KEJADIAN RISIKO TINGGI KEHAMILAN DI KLINIK PRATAMA SUNGGAL MEDAN TAHUN 2018 - Parida Hanum (Jurnal Maternitas Kebidanan, 2018)
Pregnancy is a period starting from conception to the birth of the fetus, pregnancy lasts for 280 days, calculated from the first day of the last period. High-risk pregnancy is a pregnancy that has a greater risk than usual (both for the mother and baby) which can lead to illness or death before and after childbirth. The purpose of this study was to determine the relationship between knowledge and attitudes of pregnant women with high-risk pregnancy events at Klinik Pratama Sunggal Medan in 2018. This type of research was analytical with cross sectional design. The population in this study were all pregnant women as many as 126 people. The sampling technique in this study was determined by Systematic Random Sampling. The sample in this study were 21 people. Chi square test results of the relationship between knowledge and attitudes of pregnant women with high risk pregnancy events based on variable knowledge with significance level (α) = 0.05 and df = 2 that is p value = 0.004 (p <0.005), which means that Ho is rejected by Ha accepted. Based on the attitude variable that is p value = 0,000 (p <0.005), meaning that Ho is rejected by Ha accepted. The conclusion of the study is that there is a relationship between knowledge and attitudes of pregnant women with high-risk pregnancy events at Klinik Pratama Sunggal Medan in 2018. It is expected that pregnant women with less knowledge can increase knowledge about the high risk of pregnancy